PENAMBAHAN FLY ASH PADA BETON BERBAHAN TAMBAH SP 1,5% - Ilhamsaid, Trio Aldy (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2024)
ABSTRACT : Numerous research and experiments in the field of concrete have been conducted, aiming to achieve high-quality concrete by enhancing the quality of its constituent materials, such as the hardness of aggregates and the fineness of cement. Concrete quality improvement can be achieved by incorporating partial cement replacement materials, such as fly ash, and chemical additives, including superplasticizers. The primary objective of this study is to determine the optimal concrete mix ratio and assess the compressive strength of concrete utilizing superplasticizers and fly ash. At 28 days of age, the maximum compressive strength was achieved in concrete with a 15% fly ash mix, yielding 406 kg/cm2, compared to standard concrete with 0% fly ash, which had a compressive strength of 379 kg/cm2. The compressive strength for a 5% fly ash mix was 356 kg/cm2, and for a 10% fly ash mix, it was 383 kg/cm2. This study demonstrates that concrete with a 15% fly ash substitution at 28 days of age produces higher compressive strength than 5% and 10% fly ash substitutions. There was a 1.09% increase in compressive strength for the 10% fly ash variation and a 7.29% increase for the 15% fly ash variation. From the results obtained, the most optimal variation was the 15% fly ash substitution for the compressive strength of concrete at 28 days of age.Kata kunci : Concrete, Fly ash, Compressive Strength, Superplasticizer ABSTRAK : Beberapa riset dan eksperimen di bidang beton telah banyak dilakukan salah satu upaya untuk mendapatkan beton mutu tinggi itu adalah dengan meningkatkan mutu material pembentuknya, misalnya kekerasan agregat dan kehalusan semen. Peningkatan mutu beton dapat dilakukan dengan memberikan bahan pengganti sebagian semen, diantaranya adalah abu terbang (fly ash) dan bahan tambah kimia diantaranya superplasticizer. Tujuan utama dari penelitian ini adalah untuk mendapatkan perbandingan campuran beton dan mengetahui besar kuat tekan beton yang telah menggunakan zat kimia superplasticizer dan fly ash. pada umur 28 hari Kuat tekan maksimum dicapai pada beton dengan campuran fly ash 15% sebesar 406 kg/c , sedangkan beton normal 0% kuat tekan beton sebesar 379 kg/c , untuk campuran fly ash 5% kuat tekan beton sebesar 356 kg/c dan campuran fly ash 10% kuat tekan beton sebesar 383 kg/c . Dari penelitian ini beton yang diberi abu terbang sebanyak 15% pada umur 28 hari menghasilkan kuat tekan yang lebih tinggi dibandingkan dengan subtitusi fly ash 5%,10%, Terjadi peningkatan kuat tekan beton sebesar 1,09% pada variasi BFA 10%, peningkatan kuat tekan beton sebesar 7,29% pada variasi BFA 15%. Dari hasil yang dilakukan dari tiga variasi menggunakan fly ash dalam beton didapat variasi yang paling optimum berada pada subtitusi fly ash 15% pada kuat tekan beton umur 28 hari.Kata Kunci : Beton, Fly ash, Kuat Tekan, Superplasticizer